A 3D approach to model the taper of irregular tree stems: making plots biomass estimates comparable in tropical forests. Issue 8 (2nd November 2021) - Bauwens, S.; Ploton, P.; Fayolle, A.; Ligot, G.; Loumeto, J. J.; Lejeune, P.; Gourlet‐Fleury, S.
Abstract: In tropical forests, the high proportion of trees showing irregularities at the stem base complicates forest monitoring. For example, in the presence of buttresses, the height of the point of measurement ( H POM ) of the stem diameter ( D POM ) is raised from 1.3 m, the standard breast height, up to a regular part of the stem. While D POM is the most important predictor for tree aboveground biomass (AGB) estimates, the lack of harmonized H POM for irregular trees in forest inventory increases the uncertainty in plot‐level AGB stock and stock change estimates. In this study, we gathered an original non‐destructive three‐dimensional (3D) data set collected with terrestrial laser scanning and close range terrestrial photogrammetry tools in three sites in central Africa. For the 228 irregularly shaped stems sampled, we developed a set of taper models to harmonize H POM by predicting the equivalent diameter at breast height (DBH′) from a D POM measured at any height. We analyzed the effect of using DBH′ on tree‐level and plot‐level AGB estimates. To do so, we used destructive AGB data for 140 trees and forest inventory data from eight 1‐ha plots in the Republic of Congo. Our results showed that our best simple taper model predicts DBH′ with a relative mean absolute error of 3.7% ( R 2 = 0.98) over a wide D POM range of 17–249 cm. Based on destructive AGB data, we found that the AGB allometric model calibrated with harmonized H POM data was more accurate than the conventional local and pantropical models. At the plot level, the comparison of AGB stock estimates with and without H POM harmonization showed an increasing divergence with the increasing share of irregular stems (up to −15%). The harmonization procedure developed in this study could be implemented as a standard practice for AGB monitoring in tropical forests as no additional forest inventory measurements is required. This would probably lead to important revisions of the AGB stock estimates in regions having a large number of irregular tree stems and increase their carbon sink estimates. The growing use of three‐dimensional (3D) data offers new opportunities to extend our approach and further develop general taper models in other tropical regions.